Dietary Intake and Nutrients Adequacy among Young Adults with Sickle Cell Disease in Ile-Ife, Southwest Nigeria (African Journal of Biomedical Research, 2024)
Sickle cell disease (SCD) is a chronic and genetically mutated disease seen among the African descent, of which the need to study the nutritional status and the socio-demographic characteristics is a challenge. The aim of the study was to determine the dietary intake, level of nutritional status, and sociodemographic characteristics of people with sickle cell disease in Ile-Ife, Osun State, Nigeria. The study involved 100 participants, 50 in the test group (Hb SS patients) and 50 control (other genotypes/non-Hb SS patients) in the control group, recruited at the Obafemi Awolowo University’s health centre in Ile- Ife. A questionnaire was issued to gather information on participants.  Dietary data were obtained by the socio-demographic using 24-hour dietary recall, food frequency questionnaire was distributed to the participants. Characteristics, including their body mass index (BMS) height and weight were measured. From the study, about 76.3% of the respondents did not meet the total calorie needed while 23.7% met the expectation of total calorie needed daily. Proteins and carbohydrate as a major micronutrient met the requirement 54.6% and 93.8% respectively. Fibre intake was grossly inadequate with 80.4%, mineral salts and vitamins showed inadequate intake, most especially, folate, retinol, beta carotene and vitamin D. It is evident that nutritional management should go with medical care provided to patients with sickle cell disease. The nutritional management should also focus on conscious selection of food to ensure adequacy of both macronutrients and micronutrients necessary for maximum functioning of the body and maintaining good nutritional status.